1997
DOI: 10.1074/jbc.272.37.23382
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on the Motif YIPP for the Physical Association of Jak2 Kinase with the Intracellular Carboxyl Tail of the Angiotensin II AT1 Receptor

Abstract: Angiotensin II is the effector molecule of the reninangiotensin system. Virtually all of its biochemical actions are mediated through a single class of cell-surface receptors called AT 1 . These receptors contain the structural features of the seven-transmembrane, G-proteincoupled receptor superfamily. Angiotensin II, acting through the AT 1 receptor, also stimulates the Jak/STAT pathway by inducing ligand-dependent Jak2 tyrosine phosphorylation and activation. Here, we show that a glutathione S-transferase fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(134 citation statements)
references
References 26 publications
2
131
0
1
Order By: Relevance
“…After the initial report of induction of the JAK-STAT pathway by the AT1 receptor, Marrero et al [38] demonstrated that it interacts directly with JAK2 kinase, providing the mechanism of JAK-STAT activation. Subsequently, they proposed that JAK2 is associated with the AT1A receptor through the Tyr319Ile320Pro321Pro322 (YIPP, Fig 3) sequence within the proximal carboxyl-terminal region of AT1A receptor [59]. While this YIPP motif may function as a SH2 targeting sequence upon phosphorylation of Tyr319, JAK2 contains no SH2 domains that could putatively mediate the association.…”
Section: Signaling Transduction Pathways Of the At1 Receptormentioning
confidence: 99%
“…After the initial report of induction of the JAK-STAT pathway by the AT1 receptor, Marrero et al [38] demonstrated that it interacts directly with JAK2 kinase, providing the mechanism of JAK-STAT activation. Subsequently, they proposed that JAK2 is associated with the AT1A receptor through the Tyr319Ile320Pro321Pro322 (YIPP, Fig 3) sequence within the proximal carboxyl-terminal region of AT1A receptor [59]. While this YIPP motif may function as a SH2 targeting sequence upon phosphorylation of Tyr319, JAK2 contains no SH2 domains that could putatively mediate the association.…”
Section: Signaling Transduction Pathways Of the At1 Receptormentioning
confidence: 99%
“…1 The abbreviations used are: SH2, Src homology 2; PLC, phospholipase C; Ang II, angiotensin II; VSMC, vascular smooth muscle cells; IP 3 , inositol 1,4,5-trisphosphate; PIP 2 , phosphatidylinositol 4,5-bisphosphate; PP1, 4-amino-5-(4-methylphenyl)-7-(t-butyl)pyrazolo-tyrosine phosphorylation, activation, and association of JAK2 with the receptor (10). JAK2-receptor association appears to depend on a YIPP motif in the C-terminal intracellular domain of the AT 1 receptor that is identical to the PLC␥1 SH2 domain binding site identified in the platelet-derived growth factor receptor (11). Because JAK2 does not contain any SH2 domains, the finding that JAK2 associates with this motif in the AT 1 receptor was initially puzzling.…”
mentioning
confidence: 92%
“…Point mutations and deletional mutations were introduced into the constructs as described previously (11). The sequences of all DNA constructs were verified by DNA sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
“…68 A physical association between Jak2 kinase and a part of the intracellular carboxy tail of the AT 1 receptor has been shown. 69 Very recently it has been shown that Ang II mediates the Jak/STAT pathway under pathological conditions. 70 In contrast to the AT 1 receptor, much less is known about the structural and functional properties of the AT 2 receptor, which has been cloned recently from the mouse, rat, and human.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 99%